The Impact of Car Pollution on Infant and Child Health: Evidence from Emissions Cheating - Alexander, Diane; Schwandt, Hannes (Review of Economic Studies, 2022)
Abstract In 2008, Volkswagen introduced a new generation of “Clean Diesel” cars and heavily marketed them to environmentally conscious US consumers. Unknown to the public, these cars were anything but clean, emitting pollutants up to 150 times the level of comparable gas-fuelled cars. We study the rollout of these emissions-cheating diesel cars across the United States from 2008 to 2015 as a natural experiment to examine the impact of moderate levels of car pollution on infant and child health in the general population. Using the universe of vehicle registrations, we find that an additional cheating diesel car per 1,000 cars increases \ mathrmPM_2.5, \ mathrmPM_10, and ozone by 2, 2.2, and 1.3%, respectively, while the low birth weight rate and infant mortality rate increase by 1.9 and 1.7%, respectively. Similar impacts are found for acute asthma attacks in children. These health impacts occur at all pollution levels and across the socioeconomic spectrum.